Resource Allocation Schemes Between Multi-Hop Backhaul Network and Access Network - Hongtao Yang; Yehui Liu; Yu'e Song; Shewen Sun; Lin Liu (Dianxin kexue)
A non-contention in-band multi-hop system based on OFDM was built. Two configurations of two-hop relay network were proposed and comparatively analyzed. The resource allocation issue between multi-hop backhaul network and access network was investigated. The relay backhaul network and access network share the same resource. By using calculation and a static system level simulation, the relationship among resource allocation results of the relay schemes, cell coverage and channel status was revealed.